Studying the creativity-based learning model combined with online lessons to promote creativity on principles of art. For 2nd year Vocational Certificate students - awaekaji, elafee; Napapong, Wichai; Waedramae, Mahdee; Kaosaiporn, Opas (Al-HIKMAH Journal, 2024)
This research aims to study an online lesson within creative thinking course for second-year vocational certificate students. To compare creativity scores, before and after using the developed learning model, among second-year vocational certificate of majoring in Computer Business at Satun Technical College, totaling 32 members, by using a one-group pretest-posttest design within a 12-hour research periods. The research tools included the management plan of an online lesson within creative thinking course and online lessons, the Test for Creative Thinking—Drawing Production (TCT-DP) by Jellen and Urban, by using standard deviation for analyzing the data, and a T-test dependent group. The components of study an online lesson within creative thinking course for second-year vocational certificate students included 1.1 teaching tools 1.2 lesson content 1.3 teaching and plan management of an online lesson within creative thinking course and online lessons following process. 1.3.1 to motivate the interest of learners. 1.3.2 to question and divide into group. 1.3.3 to research and resolve. 1.3.4 to present. 1.3.5 to evaluate. 1.4 measuring and evaluating of target group with the Test for Creative Thinking – Drawing Production (TCT-DP) by Jellen and Urban. 2. An online lesson within creative thinking course students showed significantly higher creativity scores compared to before the experiment, at a statistically significant of 0.5 level.